Analysis of phased array corrosion mapping data using Probabilistic Detection (POD) method - Tai, Jan Lean; Sultan, Mohamed Thariq Hameed; Shahar, Farah Syazwani (Universiti Putra Malaysia Press, 2025)
Phased Array Corrosion Mapping (PACM) has emerged as a powerful tool for detecting localized corrosion in industrial settings, particularly in the petrochemical industry. However, its application has been limited to plant operating temperatures within the recommended range for on-stream ultrasonic testing. This study addresses this gap by conducting a comprehensive Probability of Detection (POD) analysis using the MH1823 POD software, following the guidelines of MIL-HDBK-1823A (Department of Defense Handbook, 2009). The binary hit/miss method was employed to evaluate the accuracy of PACM on carbon steel (CS) and stainless steel (SS 304 and SS 316) surfaces at elevated temperatures up to 250 °C. Experimental results demonstrated successful detection of all flat-bottom-hole (FBH) indications, with deviations categorized as “miss” when exceeding 10% of the designed dimension. The POD curves revealed robust detection capabilities across various temperatures, with distinct clusters exhibiting different a50, a90, and a90/95 values. These findings underscore the reliability and efficacy of PACM in high-temperature applications, offering a significant advancement in non-destructive testing (NDT) for the petrochemical industry. The study highlights the potential of PACM to enhance turnaround maintenance (TAM) by enabling accurate on-stream inspections, thereby reducing downtime and increasing operational efficiency. Future research should explore the “â versus a” method to further enhance the accuracy and understanding of PACM in NDT applications.